Dieffenbachia seguine extract nanoemulsion as an intranasal inflammation-inducing agent in rats - Sa'diah, Siti; Leong , Ke Yong; Mayasari, Ni Luh Putu Ika; Widi, Leliana Nugrahaning; Alfarisi, Hamzah (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2025)
Background Dieffenbachia seguine (Jacq.) Schott, commonly known as the dumb cane, is a tropical ornamental plant known for its toxic and proinflammatory properties. Its potential as a natural inducer of inflammation warrants further investigation, particularly via the intranasal route. Objective This study aimed to evaluate the proinflammatory effect of D. seguine leaf extract nanoemulsion by measuring the levels of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in bronchoalveolar lavage fluid (BALF) following intranasal administration in rats. Methods Wistar rats (n= 24) were divided into six groups: water for injection (WFI, negative control); emulsion base; lipopolysaccharide (LPS, positive control); and D. seguine extract nanoemulsions at concentrations of 1%, 2%, and 4%. Each rat received an intranasal instillation, and IL-6 and TNF-α concentrations in the BALF were quantified using ELISA. Results Only the 4% D. seguine nanoemulsion group showed a significant increase in IL-6 and TNF-α levels compared to the control. Lower concentrations (1% and 2%) did not induce significant cytokine elevation. All treatment groups showed significantly lower cytokine levels than the LPS group. Conclusion D. seguine extract nanoemulsion at 4% concentration demonstrates potential as a natural inflammation-inducing agent via the intranasal route, although its effect remains lower than that of LPS.